Badi al-Zaman bin al-Razzaz al-Jazari and his role in technological improvement in contemporary world (Journal of Imam Al-Kadhim College, 2024)
AbstractThe early Muslims contributed to building our current civilization. If it were not for the innovations of Islamic civilization, our contemporary civilization would have been delayed by several centuries, The aim of the current research is to identify an important aspect in the history of technology, which is to reveal the role of the Muslim scientist and creative mechanical engineer (Ibn al-Razzaz al-Jazari) in technological development in the contemporary world. And his combination of theoretical and practical aspects, the researchers followed the historical, descriptive, analytical and inductive approach to achieve the goal of the research. The researchers discussed his experimental scientific approach, his most prominent designs and inventions, their role in the technological development that we witness today and the practical applications of Al-Jazari’s innovations in our contemporary life. The researchers concluded that the Arab scientific heritage had a great impact in the progress of the scientific movement and its arrival to what it has reached now, and that much of what is stated in the books on the science of tricks are basic rules of science that scholars cannot do without. He invented water pumps, many musical instruments, water clocks, and the elephant clock, He invented water pumps, many musical instruments, water clocks, and the elephant clock, and he was also interested in scientific issues of hydraulics and self-propelled machines, Al-Jazari’s science was one of the foundations of the scientific renaissance in Islamic civilization, which later spread to Europe, with the recognition of many Western scholars. The impact of his inventions can be seen in the designs of steam engines, internal combustion engines, robots, and others .Finally, the two researchers presented a number of recommendations.